Motor Vehicle Tax Compliance Levels: An Empirical Study And The Determining Factors - Surjanti, Lulus Prapti N. S.; Nugroho, Dwi Widi Pratito Sri; Sulistyawati, Ardiani Ika (Economics and Business Solutions Journal, 2018)
Tax is the biggest income for the state and one of taxes which imposed on taxpayers is motor vehicle tax. Normatively, for all citizens who have fulfilled the requirements as taxpayers and have motor vehicles, they should not forget to pay the tax. But in reality, there are still many taxpayers who have not complied and fulfilled their tax obligations. The aim of this study is to analyze the effect of the application of administrative penalty, awareness of taxpayers, interest rates on tax penalties, and tax payment procedure on the level of taxpayer compliance. We used accidental sampling method on motor vehicles tax payer to determine the sample. There are 144 taxpayer respondents who are willing to participate and whose data can be processed. Multi linear regression was used to test the hypothesis. The findings of this study indicate that the interest rates on tax penalties have the greatest influence on motor vehicle taxpayer compliance. While the awareness factor of taxpayers actually has the smallest influence on taxpayer compliance.